Estudio de factibilidad para la implementación de un restaurante de apetitivos tradicionales lojanos con entrega a domicilio, en la ciudad de Loja. - Aguinsaca González, Juan Leonardo (2012)
Despite being a small country, gastronomy of Ecuador is very diverse, this is because within the country there are four natural Regions (Coast, Sierra, Amazon and Galapagos Islands) which have different customs and traditions. Based on the country's natural regions are subdivided different typical dishes and ingredients. In the Andean region and Sierra highlights the presence of popular dishes such as guinea pig, humitas, tamales, etc. This region has developed a wide and diverse gastronomic culture, which can be subdivided according to each province or region. Such is the case of the city of Loja thanks to its geographic variety, cultural and ethnic has generated a variety of traditional dishes or appetitive, desired by all and sundry. Microenterprise activities, is one of the Principles to generate employment and to stimulate the economy. In our town there are very few restaurants that properly applied for management processes, for this reason and the importance of not losing our eating habits, was conducted the feasibility study for the implementation of a traditional Loja’s restaurant appetitive, home delivery in the city of Loja, in the Valley sector. Restaurant to become "Traditional Appetizers Lojanos", aims to: be a company recognized for its excellent service, leadership and competitiveness, achieving a position in the local and national market, so as also to make our customers enjoy their stay in our restaurant with family and friends, without losing its spirit Lojano, enjoying our infrastructure to make them remember the "Loja of Yesteryear," among others. This restaurant is basically dedicated to making and selling traditional Lojanos appetitive as: Repe, Fresh Figs, Mote Pillo, Sambo with milk, and Morocho. For the development of this research work we applied different methods and techniques such as deductive method helped establish objectives; the analytical method that we helped to formulate conclusions and recommendations through the collected information, likewise used as observation techniques allowed us to determine which aspects of the development of various appetitive; the three hundred ninety-nine surveys were applied to potential customers, allowed to determine the demand for our product and the interview was applied to nineteen different restaurants owners helped us determine the competition aspects of our business. With the completion of market research identified the potential demand for traditional appetitive Lojanos, the same as was 119,181 (population) over 18 years of urban parishes of the city of Loja. It should be noted that the potential demand we assume that each person consumes an appetitive, which is why we take the entire population. The current demand is real or 104,844 people. Effective demand is 84,829 people. According to surveys it was determined that the offer is sites that offer some traditional appetitive Loja, which provide a number of 19 stores known, as: Tamal Lojano, Restaurante Familiar, El Cafecito, inter alia. The analyses of supply and demand determine the unmet demand allowed, so we have: Repe for unmet demand is 713752; for fresh figs is 590668; for mote pillo is 317408; for sambo with milk is 279604 and for morocho is 188708. The restaurant's hours will be from 09h00 to 18h00 from Wednesday to Sunday. On the product side, these will be prepared with carefully selected raw materials and excellent quality, which will be purchased in local markets will be made by Radio advertising and placed advertisements in the newspaper La Hora, so too, the restaurant will have a label and logo. Our restaurant will be located in the area of Valley in Guayaquil Street and Avenue Banks of Zamora, this place is easily accessible vehicle and recognized as a tourism sector that focuses a lot of food places. Submit to a limited liability company with an investment of $ 20.222,82, this company will have two partners who bring in $ 11.222.82. The restaurant dedicated to making and selling traditional appetitive Loja will last for 10 years. It has the organizational design of a functional, structural and positional as well as the preparation of a manual of functions that will allow a good development of activities and tasks of staff. With the economic - financial study established the price for each of the appetitive: repe for the price is $ 0.80, $ 0.40 fresh figs; mote pillo $ 1.20, $ 0.70 sambo milk; morocho $ 0, 70. Likewise, it was determined the equilibrium point for the first year that function of installed capacity is 35.10% and sales function is $ 27.864,38. According to the financial analysis: Net Present Value (NPV) of the project is $ 110.683,97 dollars, ensuring a return on the value of the company at the end of its useful life (10 years). Internal Rate of Return (IRR) of investment is 29.65% which is located well above the interest rate is 11.20%. The Benefit Cost ratio reaches $ 1.53, what does it mean that for every dollar of investment you get $ 0.53 profit, likewise, accepts a project cost increase of 25% and a decrease in revenues of 20% and finally the Period of Investment Recovery The research project is 1 year, and month and 24 days. results demonstrate the feasibility of implementing the project, since it ensures profitability for investors and on the other hand allows for socio - economic and business in the city of Loja, likewise, would constitute a source of employment.